TEMPORAL AND SPATIAL VARIATIONS OF HEAVY METALS IN SHELLFISH IN BANTEN BAY: VARIASI TEMPORAL DAN SPASIAL LOGAM BERAT PADA KERANG DAN KEPITING DI TELUK BANTEN - Dinulislam, Annisa; Salsabilla, Tsalista; Melinda, Tresna; Sulistyowati, Dwi Indah; Noviani, Ertika; Fatryani, Dita; Febrianessa, Nadya; Nedya, Hanifah; Sulistiono, Sulistiono (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Banten Bay is a busy water area with diverse activities, including capture fisheries, aquaculture, marine and land transportation, and industry, which are estimated to generate significant amounts of heavy metals that enter the water and accumulate in fish and shellfish. Some fishery commodities commonly found in Banten Bay included shellfish, such as blood cockles, green mussels, mud crabs, and blue swimming crabs. The study aims to monitor heavy metal contamination variations spatially and temporally of the shellfish in Banten Bay. Biota samples were taken for 6 months in Cengkok Coastal Waters (March–August 2019) and 3 months in Bojonegara Coastal Waters (August–October 2020). The heavy metal content was determined using an atomic absorption spectrophotometer (AAS). Pb and Cd concentrations in the flesh of the shellfish (blood cockles, green mussels, mud crabs, and blue swimming crabs) from the Cengkok and Bojonegara Coastal Waters ranged from 0.001 to 0.070 ppm and from